2006
DOI: 10.1007/s11373-005-9066-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression and characterization of the zebrafish bram1 gene, a BMP receptor-associated molecule

Abstract: We have identified a cDNA clone encoding BMP receptor-associated molecule 1 (BRAM1) from the zebrafish expressed sequence tag (EST) database. The 2606 bp full-length bram1 cDNA was cloned, and further confirmed by nucleotide sequencing. The zebrafish sequence encodes a protein of 195 amino acids with an evolutionarily conserved MYND domain, which displays approximately approximately 98% homology with human and mouse BRAM1, and approximately approximately 64% homology with C. elegans BRA-1 and BRA-2. The bram1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…To test these hypothesis, we firstly examined the gene expression pattern of mga, bs69 , and bmpr1a during zebrafish early embryogenesis. The three genes have similar expression patterns from blastula to late organogenesis as reported ( Wu et al, 2006 ; Rikin and Evans, 2010 ; Smith et al, 2011 ). During gastrulation, both bmpr1aa and mga transcription levels are high, whereas bs69 transcript levels are relatively low.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…To test these hypothesis, we firstly examined the gene expression pattern of mga, bs69 , and bmpr1a during zebrafish early embryogenesis. The three genes have similar expression patterns from blastula to late organogenesis as reported ( Wu et al, 2006 ; Rikin and Evans, 2010 ; Smith et al, 2011 ). During gastrulation, both bmpr1aa and mga transcription levels are high, whereas bs69 transcript levels are relatively low.…”
Section: Resultssupporting
confidence: 79%
“…It has been previously shown that mammalian MGA directly interacts with BS69, and that BRAM1, a possible spliced form of BS69, may be involved in the regulation of BMPR1A activity ( Kurozumi et al, 1998 ; Ansieau and Leutz, 2002 ; Velasco et al, 2006 ; Wu et al, 2006 ). Therefore, we speculated that Mga may modulate Bmpr1a activity through Bs69 in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is a set of intracellular proteins that act as signal transducers or regulators of BMP signaling. Among them, BMPRIa interacts with the TGFβ-activated kinase (TAK) binding protein 1 (TAB1) through the BMP receptor-associated molecule 1 (BRAM1), which downregulates BMP-mediated Smad signaling [59]. Likewise, the X-chromosome-linked inhibitor of apoptosis (XIAP) connects BMPRI with TAB1 and may act as a positive regulator of MAP kinase signaling [60].…”
Section: Bmp Signaling Pathwaymentioning
confidence: 99%
“…To date, two homologs of BRAM1 in C. elegaus (BRA-1 and BRA-2) have been identified, and BRA-1 negatively regulates TGF-b signaling by blocking physical interaction between the type 1 receptor and Smads [17]. Wu et al [18] isolated zebrafish bram1, and found that BRAM1 directly interacts with the BMP receptors resulting in down-regulation of BMP signaling in cells.…”
Section: Isolation Of Zebrafish Bmp Receptor-associated Moleculementioning
confidence: 99%